Decisión y forma social. Más allá de Schmitt, Hegel - Bruna Castro, Carolina (Conceptos Históricos, 2020)
The aim of this paper is to argue that the concept of decision is not equivalent to an arbitrary action. To define the concept of decision I consider fundamental the notion of exception in relation to contingent reality since deciding implies organizing our relationships with other people and the environment. In the context of these concepts, arises what we call subjectivity, which is not a reference to polarized individuality but to human relationships. To illustrate this characteristic, my argument considers the work of Carl Schmitt and Hegel but aims to go beyond them. In reference to Schmitt, I use the interpretation of Giuseppe Duso, who highlights the understanding of subjectivity from the perspective of plurality and relationships, from which the idea of decision arises. With respect to Hegel I consider the Philosophy of Rights and the reference to Antigone appearing in the Phenomenology of the Spirit.